Crazy rich Asian countries? The impact of FDI inflows on the economic growth of the economies of Asian countries: evidence from an NARDL approach - Goh, Lim Thye; Kaliappan, Shivee Ranjanee; Lin, Woon Leong (Universiti Putra Malaysia Press, 2020)
FDI inflows are often regarded as the engine of economic growth, where an increase in FDI leads to higher productivity and higher international trade. Recognising that financial crises, political instability and trade wars may shape the asymmetric behaviour of FDI inflows, this paper utilises the NARDL model by Shin et al. (2014) over the period 1970-2017 to examine the asymmetric cointegration between the FDI inflows and economic growth of three economic nation groups in the Asian region. The empirical results indicate that 1) there is significant evidence of the asymmetric effects of FDI inflows on the economic growth of Asian developing countries. More specifically, an increase in FDI inflows tends to lead to an increase in economic growth, while a reduction in FDI inflows is detrimental to economic growth. 2) a higher human capital index and capital stock in the host country promotes economic growth.